EVALUASI PERANAN KANTOR PELAYANAN PAJAK (KPP) PRATAMA BATU BERDASARKAN PERATURAN DIREKTORAT JENDERAL PAJAK - Agung A.R, R. Firman (Jurnal Mahasiswa Perpajakan, 2015)
Taxation sector is a source of reception in Indonesia, but the country’s reception is not optimal. Direktorat Jenderal Pajak (DJP) (Directorate General of taxes)  made efforts in taxation reception optimization by formulating and implementing standardization in the field of taxation. Kantor Pelayanan Pajak (KPP) Pratama Batu (Tax Service Office) as instances of vertical DJP on role in the area, has a role in giving understanding of taxation, administrative and procedural aspects of taxation. Therefore needs to evaluate the implementation of the role to determine compatibility with DJP’s standardization. This research used the qualitative approach with a descriptive method. Location research in the KPP Pratama Batu. Methods of analysis using interactive model from Miles Huberman. Results  of research, KPP Pratama Batu implement it’s role through socialization activities, service of SPT reporting, sanction enforcement actions and penalties. Public awareness and action through sanctions enforcement inspection has been carried out in accordance with the rules of taxation but the granting of SPT Tahunan (Yearly reporting service)  is not appropriate with the regulations because the layanan pojok (service corner) has not yet been implemented and the car service tax is hampered caused the facility not owned Keywords: Evaluation, Role, Kantor Pelayanan Pajak Pratama